Tuberculous meningitis: evaluation of polymerase chain reaction (PCR) as a diagnostic tool – a pilot study. - Geib, Guilherme; Dora, José Miguel; Chakr, Rafael; de Paris, Fernanda; Mombach, Alice Beatriz; Lutz, Larissa; Souza, Carolina Fischinger Moura de; Goldani, Luciano (Clinical and Biomedical Research, 2008)
Meningitis is a severe and potentially fatal form of tuberculosis. The diagnostic workup involves detection of acid-fast bacilli in the cerebrospinal fluid by microscopy or culture. However the difficulty in detecting the organism poses a challenge to diagnosis. Use of polymerase chain reaction (PCR) in the diagnostic approach to Mycobacterium tuberculosis (MTB) meningitis has been reported as a fast and accurate method, with several commercial kits available. As an alternative, some institutions have been developing inexpensive in-house assays. In our institution, we use an in-house PCR for tuberculosis. The performance of our PCR for the diagnosis of MTB meningitis was analyzed in 148 consecutive patients, using MTB culture as the gold standard. Sensitivity of cerebrospinal fluid PCR for the diagnosis of MTB meningitis was 50%, specificity was 98.6%, and concordance with culture was 96% (kappa = 0.52). The performance of our PCR is similar to that obtained with the available commercial kits.